miR-149 Alleviates Ox-LDL-Induced Endothelial Cell Injury by Promoting Autophagy through Akt/mTOR Pathway - Zhongsheng Zhu; Jinyu Li; Rui Tong; Xiaorong Zhang; Bo Yu (Cardiology Research and Practice)
Background. Atherosclerosis is a chronic process that takes place in the vascular wall and causes various cardiovascular diseases (CVDs). Micro-RNA-149 (miR-149) mediates many physiological and pathological processes, including atherosclerosis. However, it is unclear about the roles of miR-149 in endothelial injury. Here, we explored the protective effect and related mechanism of miR-149 in endothelial cells induced with oxidized low-density lipoprotein (ox-LDL). Methods. Human endothelial cell lines (HUVECs) were exposed to ox-LDL to induce endothelial injury. Cell viability was determined by the CCK-8 assay. Autophagy was detected by immunofluorescence. RT-qPCR and western blot were carried out to determine the mRNA and protein expressions of Akt and mTOR. Results. The miR-149 level in HUVECs was reduced by ox-LDL (100 μg/mL) incubation in a time-dependent manner. miR-149-mimic transfection markedly protected HUVECs from ox-LDL-induced injury, with increased cell viability and reduced caspase-3 activity. miR-149 mimics enhanced HUVEC autophagy, which was induced initially by ox-LDL. miR-149 mimics also markedly downregulated the expression of Akt, p-Akt, mTOR, and p-mTOR in ox-LDL-treated HUVECs. The miR-149-induced protection against HUVECs injury could be reversed by cotreatment with 3-methyladenine (3-MA, an autophagy inhibitor) or insulin (an activator of Akt/mTOR pathway). Conclusions. miR-149 prevents ox-LDL-induced endothelial cell injury by enhancing autophagy via increasing Akt and mTOR expressions.